2019
DOI: 10.1080/23802359.2019.1693921
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the brown pansy butterfly, Junonia stygia (Aurivillius, 1894), (Insecta: Lepidoptera: Nymphalidae)

Abstract: The brown pansy, Junonia stygia (Aurivillius, 1894) (Lepidoptera: Nymphalidae), is a widespread West African forest butterfly. Genome skimming by Illumina sequencing allowed assembly of a complete 15,233 bp circular mitogenome from J. stygia consisting of 79.5% AT nucleotides. Mitochondrial gene order and composition is identical to other butterfly mitogenomes. Junonia stygia COX1 features an atypical CGA start codon, while ATP6, COX1, COX2, ND4, and ND4L exhibit incomplete stop codons. Phylogenetic reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Phylogenetic reconstruction employed 90 nuclear rRNA repeat sequences from 62 Junonia specimens, 19 specimens from other genera in tribe Junoniini and nine outgroup specimens from subfamily Nymphalinae (Dataverse electronic supplementary material, table S1). Our laboratory generated all of the nuclear rRNA repeat sequences, some of which were published previously [ 26 28 , 50 57 ], but are analysed in concert here for the first time, to our knowledge. When samples in the mitogenome dataset lacked GenBank Sequence Read Archives (SRAs) containing sufficient raw sequence data to assemble a nuclear rRNA repeat, they were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic reconstruction employed 90 nuclear rRNA repeat sequences from 62 Junonia specimens, 19 specimens from other genera in tribe Junoniini and nine outgroup specimens from subfamily Nymphalinae (Dataverse electronic supplementary material, table S1). Our laboratory generated all of the nuclear rRNA repeat sequences, some of which were published previously [ 26 28 , 50 57 ], but are analysed in concert here for the first time, to our knowledge. When samples in the mitogenome dataset lacked GenBank Sequence Read Archives (SRAs) containing sufficient raw sequence data to assemble a nuclear rRNA repeat, they were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Further, some phylogenetic studies of New World taxa have included GenBank sequences labelled as either Junonia evarete or Junonia genoveva , but in the absence of museum vouchers it is unclear if the source-specimens were correctly identified or if they belong to one of six other potential Junonia species [ 6 , 16 19 ]. The use of DNA barcoding [ 3 , 17 – 19 ] and later, full mitochondrial genome sequencing [ 5 , 26 28 ], confirmed that Junonia is a monophyletic clade. Although still missing species, these studies improved phylogenetic resolution over earlier studies.…”
Section: Introductionmentioning
confidence: 99%